THE APPLICATION OF SEFL DECLARE SYSTEM ON HALAL GUARANTEE SYSTEM ON MICRO AND MEDIUM ENTERPRISE - Putranto, Adik Dwi (Universitas Airlangga, 2024)
Since the introduction of micro and medium enterprise and its legal acknowledgement in Indonesia, the development of these enterprises is growing steadily fast. Upcoming micro and medium enterprise in Indonesia has grown large and spread evenly throughout Indonesian archipelago. Seeing the growth, Indonesian government tried to accommodate the growth by introducing regulation to regulate and help them grow. One of the favor given by the government is the ease of Halal Certificate for these micro and medium enterprise. Usually, the Halal Certificate will be given by assessing the business. For micro and medium enterprises, they are given the choice to ‘self-declare’ their product as Halal without going through the usual process. However, in the implementation of this system, the standardization of Halal for ‘self-declare’ system need to be set straightly as if no proper procedure is given, there will be numerous non-halal product labelled as halal through the ‘self-declare’ system. The research has shown that through proper mechanism and by abiding the procedure given by the law, the standardization of halal throughout ‘self-declare’ system could be carried out in ease.